2012
DOI: 10.1534/genetics.112.142687
|View full text |Cite
|
Sign up to set email alerts
|

Gene-Expression Changes Caused by Inbreeding Protect Against Inbreeding Depression in Drosophila

Abstract: We present a transcriptomic analysis aimed at investigating whether the changes in gene expression that occur under inbreeding generally reduce or enhance inbreeding depression. Discerning between these two alternatives can be addressed only when both changes in expression due to inbreeding and to inbreeding depression are estimated simultaneously. We used Affymetrix 2.0 arrays to study the changes in gene expression associated with both inbreeding and inbreeding depression for fitness in four sets of inbred s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 59 publications
1
27
0
Order By: Relevance
“…Recent studies showed that several pathways may be upregulated in inbred as compared with outbred Drosophila individuals, whereas others, though less commonly occurring, are downregulated (Kristensen et al, , 2006Pedersen et al, 2005;García et al, 2012). Similarly, Ayroles et al (2009) showed that inbreeding depression results in an overexpression of many genes associated with metabolism, stress or defence mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that several pathways may be upregulated in inbred as compared with outbred Drosophila individuals, whereas others, though less commonly occurring, are downregulated (Kristensen et al, , 2006Pedersen et al, 2005;García et al, 2012). Similarly, Ayroles et al (2009) showed that inbreeding depression results in an overexpression of many genes associated with metabolism, stress or defence mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…The biological material used in this work is described in [19], where a detailed description of the experimental design and main analytical tools employed can be found. Briefly, the base population was founded in November 2006 from a large sample (>1000 females) collected in a wine cellar close to Vigo (Galicia, NW Spain).…”
Section: Methodsmentioning
confidence: 99%
“…Three replicates of the outbred control were also randomly chosen for analysis. For each sample, pools of 30 males from each selected inbred subline and from the outbred controls were used for total RNA extraction and hybridization with the array as described in [19]. We only analysed gene expressions in males to avoid the source of additional experimental variance associated to post-mating gene expression changes in females [32], or to different stages of egg development in pregnant females [33].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 In recent times, however, the advent of large-scale platforms to monitor [2][3][4] We made a gene expression analysis of inbreeding in Drosophila melanogaster males using the Affymetrix Drosophila Genechip Array 2.0 and aimed to distinguish the changes that alleviate the depression from those that generate it. 5 We started with four pairs (lines) of individuals and founded 55 full-sib mating inbred sublines with each. In generation eight, the sublines showed a great variation in pupa productivity (and thus inbreeding depression), despite having the same genealogical inbreeding coefficient (around 0.7).…”
mentioning
confidence: 99%